Quality of children's death records for regionalized spaces: a methodological route - Neir Antunes Paes; Carlos Sérgio Araújo dos Santos; Tiê Dias de Farias Coutinho (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2021)
ABSTRACT: Objectives: To propose a methodological path to investigate the coverage and information filling of maternal-infant deaths recorded in the Ministry of Health's Mortality Information System for regional spaces. Methods: Four steps were proposed: 1) Assessment of the completeness of the maternal and child variables, which was measured using the deterministic linkage technique between the Mortality Information System (Sistema de Informações sobre Mortalidade - SIM) and the Live Birth Information System (Sistema de Informações sobre Nascidos Vivos - SINASC); 2) Application of the multiple imputation technique to achieve the total filling of the missing information of the variables; 3) Estimation of death coverage; 4) The Unknown Variable Information Index (Índice de Informação Desconhecida da Variável - IIDV) was measured, which represents the combined effect of data completeness and coverage of deaths. The proposal of the methodological path was exemplified for neonatal deaths in the municipalities of Paraíba that are part of the new classification proposed by the Brazilian Institute of Geography and Statistics (Instituto Brasileiro de Geografia e Estatística - IBGE), as adjacent rural areas, in three triennium periods from 2009 to 2017. Results: The percentage of matching records was 45%. Most of the variables had a percentage of non-completion below 10% and around 17% for the mother's education. Coverages ranged from 75 to 83%. The IIDV for all variables was between 21 and 36% after the linkage. Conclusion: The path of the methodological proposal proved to be effective, which can be replicated to other regions, and can be extended to other categories of deaths such as post-neonatal. The combination of the proposed procedures demands low operating costs and their uses are relatively simple to be applied by the managers and technicians of the vital statistics information systems.